2019
DOI: 10.1007/s00222-018-00849-y
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimension of planar self-affine sets and measures

Abstract: We calculate the Assouad dimension of a planar self-affine set X satisfying the strong separation condition and the projection condition and show that X is minimal for the conformal Assouad dimension. Furthermore, we see that such a self-affine set X adheres to very strong tangential regularity by showing that any two points of X, which are generic with respect to a self-affine measure having simple Lyapunov spectrum, share the same collection of tangent sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(148 citation statements)
references
References 57 publications
2
146
0
Order By: Relevance
“…Very recently, after this article was finished, Bárány, Hochman, and Rapaport showed that the dimension of planar self‐affine measures is equal to the Lyapunov dimension if the strong open set condition holds and the matrix tuple is strongly irreducible. Furthermore, we point out that, under the assumption that (v1,,vN) is linearly independent (which, in particular, forces Nd), one can prove the result of Theorem for every ergodic measure.…”
Section: Preliminaries and Statements Of Main Resultsmentioning
confidence: 99%
“…Very recently, after this article was finished, Bárány, Hochman, and Rapaport showed that the dimension of planar self‐affine measures is equal to the Lyapunov dimension if the strong open set condition holds and the matrix tuple is strongly irreducible. Furthermore, we point out that, under the assumption that (v1,,vN) is linearly independent (which, in particular, forces Nd), one can prove the result of Theorem for every ergodic measure.…”
Section: Preliminaries and Statements Of Main Resultsmentioning
confidence: 99%
“…Therefore without loss of generality we can assume it is positive. Therefore ψ A (1) so it is sufficient to show that log(1 + t 3 (t−t 1 ) t 1 t 3 −t 2 t 4 ) can be written as a convergent power series in (t − t 1 ). Indeed…”
Section: 2mentioning
confidence: 99%
“…A large part of the dimension theory of self-similar sets is well understood. For example, if we denote the contraction ratios of the similarities S (i) by r := {r i } i∈I then under suitable separation assumptions on the pieces {S (i) (F )} i∈I it is well known that all notions of dimension of F coincide and the common value is given by the solution s to the pressure-type formula P r (s) = i∈I r s i = 1 (1) Date: 17th April 2019. 1 which we call the similarity dimension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations